ANALISIS MAKNA SIMBOLIK DALAM TRADISI PANCENAN DI DUKUH JATEN KABUPATEN SRAGEN - Oktaviana, Indi; Sulaksono, Djoko; Veronika, Prima (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2025)
This research aims to (1) find out the ubarampe in the Pancenan tradition of Dukuh Jaten, Sragen Regency (2) analyze the symbolic meaning in the ubarampe of the Pancenan tradition in Jaten Dukuh, Sragen Regency. The data used is photo documentation of Ubarampe while the research data source is the results of interviews. The data collection technique uses documentation about the Pancenan tradition of ubarampe. The analytical technique used by the Miles and Huberman interactive model is divided into four stages (1) The appropriate data analysis technique used for the descriptive type is through four activity flows, namely (1) collecting data, (2) data reduction, (3) presenting data, and (4) drawing conclusions or verification. Based on the results of the analysis, it was found that the research results (1) mentioned the form of ubarampe in the Jenang Sura tradition, (2) explained the symbolic meaning contained in the ubarampe of the Pancenan tradition.